1996
DOI: 10.1128/mcb.16.7.3523
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Involvement of trans-Acting Factors in Selection of the AUG Start Codon during Eukaryotic Translational Initiation

Abstract: The molecular mechanism with which an appropriate AUG codon is selected as the start site for translational initiation by eukaryotic ribosomes is not known. By using a cell-free translation system, small RNA molecules containing single AUG codons, surrounded by various nucleotide sequences, were tested for their abilities to interfere with the translation of a reporter mRNA. RNAs containing the AUG in an ACCAUGG context (Kozak consensus sequence) were able to inhibit translation of the reporter mRNA. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 42 publications
3
34
0
Order By: Relevance
“…La was easily detected in the S130, which was the starting material from which it was purified. Some La was also detected in polysomes, which is consistent with the binding of La to 18S rRNA (50) and to cell mRNAs (38). La in the S130 appeared to migrate slightly faster than purified La.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…La was easily detected in the S130, which was the starting material from which it was purified. Some La was also detected in polysomes, which is consistent with the binding of La to 18S rRNA (50) and to cell mRNAs (38). La in the S130 appeared to migrate slightly faster than purified La.…”
Section: Resultssupporting
confidence: 60%
“…We do not know if La is actually bound to histone mRNA or acts indirectly, although other in vitro studies suggest that La can bind to strong translation initiation regions of mRNAs (38). However, La does not appear to affect the half-lives of FIG.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…By using a mammalian cell-free translation system, several protein factors, including the La autoantigen, were found, in mRNA competition experiments, to bind specifically to the initiation codon of small RNAs only if embedded in a favourable ACCAUGG context (McBratney and Sarnow, 1996). Svitkin et al (1996) recently showed that several eukaryotic RNA-binding proteins (including La, pyrimidine-tract-binding protein and others) can bind to various regions within mRNAs in vitro and perhaps block potential 'false' internal start sites of capped eukaryotic transcripts.…”
Section: 'Consensus Sequences' That Influence the Selection Of Initiamentioning
confidence: 99%
“…The efficient IRES evolved by picornaviruses and some cellular mRNAs indicates that eukaryotic ribosomes can also bind internally to mRNAs, perhaps requiring additional trans-acting proteins and prokaryotic-like interactions with 18S rRNA (Pilipenko et al, 1992;Jackson, 1996). Similar trans-acting proteins may also help ribosomes to recognize the correct translation initiation site or discriminate against 'false' start codons in 'capped' eukaryotic mRNAs (McBratney and Sarnow, 1996;Svitkin et al, 1996).…”
Section: Internal Ribosome Entry: An Alternative Mechanism For Selectmentioning
confidence: 99%